Prospecting and Exploration Through the Ages: Enduring Fundamentals but Changing Technologies - Hutchinson, Richard (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2001)
Summary The fundamentals that drive prospecting and exploration, i.e., the search for useful mineral materials by investigating ob-erved abnormalities, have not changed significantly through the millennia. The variety of minerals sought and the approaches used in the search, however, have increased exponentially, especially in the last century, owing to advances in many fields of science and technology, all accompanying immense growth, diversification, global expansion, and integration of the world's mineral industry. The focus of these activities has shifted continually and progressively westward from Mesopotamia through the Mediterranean basin and northwestern Europe to the Americas, then southward to Africa and Australia, but always toward little-explored or unexplored regions. Significantly, the focus of world political influence has accompanied this westward shift throughtime. Mineral wealth, derived through prospecting and exploration, is an essential basis of modern living standards and global power, an overlooked, ignored, or even forgorten relationship that meritscareful reconsideration by today's public, idealists, and politicians.